Conservative management of placenta percreta - Gavit, Yogita; Sharma, Deepika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
The incidence of placenta accreta, increta, percreta, collectively called placenta accrete spectrum disorders, has been rising dramatically over the last decade worldwide, mainly due to rising cesarean delivery rate. Antenatal diagnosis and making no attempt to remove any parts of placenta is associated with reduced levels of hemorrhage and therefore less blood transfusion. Although elective cesarean hysterectomy is the standard practice, the choice of conservative management has emerged into practice. Conservation of the uterus reduces numerous short- and long-term complications including massive blood transfusion, disseminated intravascular coagulopathy, high morbidity and mortality rates, adjacent pelvic organ damage, infection as well as long term psychological sequelae, due to loss of femininity and fertility. Hereby representing a model for the follow up of conservative management of placenta percreta. Sequential changes in symphysial fundal height, serum beta-HCG and ultrasonographic volume of the placenta mass were used as combined methods for the follow up of the case. The placental volume was calculated by using a 2-dimensional ultrasound scan by measuring the maximum length and anteroposterior and transverse diameters of the uterus and using the formula for the volume of prolate ellipsoid.